Lordships, state capacity and beyond: literacy rates in mid-nineteenth-century Valencia - Francisco J. Beltrán Tapia; Alfonso Díez-Minguela; Julio Martinez-Galarraga; Daniel A. Tirado-Fabregat (European Historical Economics Society (EHES), 2020)
In this article we explore the relationship between institutions and educational performance from a historical perspective. Relying on municipal-level information for the Spanish region of Valencia, our study explores the economic effects of the delegation of power during the ancien regime from the Crown to local elites through the establishment of lordships, compared to that remained under royal jurisdiction. We assess whether these lordships, in their late-eighteenth- century configuration, had an impact on male literacy rates in the mid-nineteenth century. We also analyse whether a negative differential effect emerged in areas that were mainly inhabited by Moriscos, populations who lived under particularly harsh conditions. In addition to this institutional diversity, we investigate whether the regulations governing the education system could have generated a negative effect due to a mismatch between the language of schooling (Spanish) and the population's language of use (Catalan). By isolating each of these effects, our findings show that literacy rates were consistently lower in Catalan-speaking lordships inhabited by Moriscos.
Keywords: N33; I24; I25; 330; Education; Institutions; Inequality; Language